1990
DOI: 10.1164/ajrccm/142.3.563
|View full text |Cite
|
Sign up to set email alerts
|

Small Airway Dimensions in Smokers with Obstruction to Airflow

Abstract: The obstruction to airflow that develops in some cigarette smokers is thought to be related to inflammation of small airways. However, the mechanism by which inflammation leads to obstruction has not been elucidated. We performed morphometry to determine if the airways of patients with obstruction were thicker than normal. Sixty smokers were selected from those undergoing resectional lung surgery. They were grouped according to their FEV1/FVC ratio (FEV1% control = 77%, FEV1 obstructed = 55%) and matched for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
2
3

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(168 citation statements)
references
References 3 publications
9
150
2
3
Order By: Relevance
“…RMANOVA analyses the patients as a continuum and thus avoids the bias that would result from forming subgroups of patients. The previous work of TIDDENS et al [9], KUWANO et al [10] and BOSKEN et al [21] found linear relationships between the square root of airway wall areas and airway size. Square root transformation of the present data (WABM, WAM, WAcart) again resulted in normal distributions of data around the linear regression lines.…”
Section: Discussionmentioning
confidence: 89%
“…RMANOVA analyses the patients as a continuum and thus avoids the bias that would result from forming subgroups of patients. The previous work of TIDDENS et al [9], KUWANO et al [10] and BOSKEN et al [21] found linear relationships between the square root of airway wall areas and airway size. Square root transformation of the present data (WABM, WAM, WAcart) again resulted in normal distributions of data around the linear regression lines.…”
Section: Discussionmentioning
confidence: 89%
“…Rather, it is influenced by several direct or indirect factors. Certainly, airway-wall thickening contributes to airway narrowing (39,40). Secretions or exudates within the airway luminal area may further contribute to airway narrowing.…”
Section: Discussionmentioning
confidence: 99%
“…Niewoehner and colleagues first demonstrated that inflammatory changes were present in the peripheral airways of young smokers who died suddenly outside of the hospital, indicating that early structural changes in the small airways developed before the diagnosis of COPD was established (17). Subsequently COPD investigators turned their attention to the inflammatory infiltrate and pathology of the small airways and verified that small airway remodeling was critical to COPD pathogenesis (18)(19)(20).…”
Section: Airways Diseasementioning
confidence: 99%
“…Some studies have found airway smooth muscle mass to be increased in COPD (18,34,35), whereas others have not (36)(37)(38). Whether or not airway hyperresponsiveness is a primary cause of fixed airflow obstruction continues to be a topic of debate.…”
Section: Smooth Muscle Hypertrophy and Airway Wall Fibrosismentioning
confidence: 99%